Limb ischemia after coil migration used for a hypogastric aneurysm embolization - Olaria, Miquel Gil; Wiesendanger, Natalia Hernandez; Hernández, Clàudia Riera; Gracia, Carlos Esteban; Pujol, Secundino Llagostera (Archives of Case Reports, 2021)
Hypogastric artery aneurysms are an uncommon entity. When the diameter achieves > 30-35 mm, they should be treated. Endovascular repair may be considered as first line therapy. One therapeutic option for internal iliac artery aneurysm exclusion is its embolization with or without covering the ostium with a covered stent. They may be some complications when it is not, as a distal coil migration that may produce ischemic symptoms. We are presenting a 73-years-old male admitted to hospital with an acute right lower limb ischemia caused by a coil migration. He recently underwent a right hypogastric artery aneurysm endovascular treatment by coil embolization without covering the hypogastric ostium with a covered stent. The patient underwent an emergency surgery to remove the coil by a transfemoral surgical approach with posterior thrombectomy of the secondary thrombus. Actually, he remains asymptomatic and with right posterior tibial pulse. Covered stent placement at the common iliac artery and external iliac artery could be the best option to avoid the risk of aneurysm rupture caused by endotension and the risk of distal coil migration.